Peran Pemerintah Daerah Dalam Pengembangan Pariwisata di Kabupaten Soppeng - Khaerul Mubarak (Departemen Ilmu Pemerintahan Fisip Unhas, 2023)
This study aims to find out how the role of the Tourism, Youth and Sports Office of Soppeng Regency in the development of Tourism Villages and the factors that influence it. To achieve this goal, qualitative research methods are used using descriptive data. Data collection techniques are observation, interviews, as well as documents and archives using qualitative descriptive analysis techniques. The results showed that the Role of Local Government in Tourism Development in Soppeng Regency from where the Regional Regulation of Soppeng Regency Number 2 of 2019 concerning Tourism Villages from the aspect of tourism village development consists of Tourism Village Institutions, Tourism Village Objects, Tourism Village Marketing, has been running well. From the aspect of Tourism Village Institutions in Mattabulu and Bule villages, Village-Owned Enterprises (BUMDES) and Pokdarwis institutions have been formed that manage tourism villages, while the tourist village objects of each village have their own charms both natural attractions and cultural tourism objects, while the marketing of tourism villages is carried out by all stakeholders, both district governments who carry out promotions in the form of advertisements and direct promotions in the form of introduction of tourist objects in Soppeng Regency and the village government promote through official website accounts and social media such as Instagram, Facebook, and Twitter of each village.